Investigation of pressure sensitive plastic flow in nanoglasses from finite element simulations. (15th April 2020) - Hirmukhe, S.S.; Prasad, K. Eswar; Singh, I.
Abstract: Finite element simulations of indentation on Sc75 Fe25 nanoglasses (NGs) and metallic glass (MG) ribbons are performed by employing extended Drucker Prager (EDP) and Von-Mises plasticity model, and pressure sensitive index, α is determined by fitting recent experimental data. It is found that yield behavior of NG is better characterised by pressure sensitive (i.e., EDP) yield criterion. In fact, α for NG is found to be around 12 0 − 20 0, while it is only 4 0 − 6 0 for MG ribbon. Further, results show that α for glassy interfaces is much higher than glassy grains of Sc75 Fe25 NG. Graphical abstract: Image, graphical abstract